Authentic video materials for developing learners’ communicative competence - Joldasbaeva, A.T; Arzieva, B.A (SCIENCE and SOCIETY, 2024)
In this article, the communicative competence of pupils aimed at improvement and development, its specific features, is described in a systematic and comprehensive way. Ideas and suggestions related to the successful communication are presented for developing the communicative competence in a foreign language.
Keywords: pedagogy; language; information; motivation; materials; teaching; approach; level; vocabulary